Effect of ammonia oxidizing bacteria communities in enriched nitrifying activated sludge and sludge from full scale wastewater treatment plants on degradation of 17α-ethynylestradiol via co-metabolism - Napasawan Khongkham (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2008